Study on Aeromonas spp. Isolated from raw and drinking water in Baghdad city - Eliwi, Sanaa; Musleh, Rashid; Sabah, Majeed; Ibraheem, Seham (Iraqi Journal of Science, 2024)
Atotal of 551 water samples drinking( five Water Treatment Plans (WTPs) and raw water( from different sites on Tigris river) were collected.According to morphological characteristics and a set of biochemical tests, one hundred twenty eight of Aeromonas spp isolates were obtained In this study The percentages of Aeromonas recovery from river water was 72.52%, from wells water was (35%).Total percentage of positive aeromonas samples of treated water(Filtration &chlorine tank, supply water of WTPs, distribution system, reserviores and other samples not related to WPTs) was 8.8%.Count of Aeromonas in positive aeromonas samples ranging from 1 to 175 cfu 100 ml.The results showed that generally no significant correlation between presence of aeromonas in distribution system water and other indicators (total heterotrophic plate counts and fecal pollution), also negative correlation between residual chlorine and recovery percentage were detected.Seasonal pattern for the incidence of isolates investigated that higher rate took place during summer months, while the lower rate occurred during winter.The results of identification to species level were: the most predominant species is A. hydrophla 63 isolates(49.21%), A. trota 21isolates(16.41%), A. veroni12 isolates(9.37%) A. salmoncida 11 isolates(8.59%), and A. schubertii, A. sobria, A. cavia four isolates for each(3.13%), and unidentified Aeromonas SPP nine isolates(7.03%). Aeromonas hydrophila isolates revealed higher resistant for most antibiotics used in the study